Simulating modelling for improving productivity of rice packaging mill - Lai, Saw Wai (2013)
In this study, it discusses about bottlenecks occurs t the Rice Packaging Line by using the simulation to improve the productivity. The scope of this study is focusing on the packaging process in the Rice Packaging Line. The aim and objectives of this study is to identify bottlenecks and increase productivity in total. The time frame given to complete this project is one year starting from the year of 2012. This study is conducted by using the ARENA simulation software to simulate the modeled process in the simulation software. It is a quantitative study in which the performance is measured by the productivity for the whole system of production line. The altering of productivity and the resource utilization are able to provide an improvement of about 40percent in the current system which is 87 packs of rice per day.